2021
DOI: 10.1097/mbc.0000000000001056
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary factor V deficiency from heterozygous mutations with a novel variant p.Pro798Leufs∗13 in the F5 gene

Abstract: To explore the causative mutation for autosomal recessive inheritance factor V (FV) deficiency in a Chinese family. Relative coagulation indexes and the FV antigen were tested by the one-stage clotting method and ELISA, respectively. At the same time, the calibrated automated thrombogram (CAT) was used to analyze the mutant protein function. All 25 exons, flanking sequences, 5′ and 3′ untranslated regions of the F5 were amplified by PCR and sequenced directly, while each suspected variant was verified by rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This may be the reason for the decrease of FV:Ag in p.Asp2222Gly and p.Arg96His heterozygotes. The p.Pro798Leufs à 13 was first identified by Deng et al 5 , which suggested that it was a disease-causing mutation and might give rise to damage to the function and structure of the FV protein. According to our protein structure model, the p.Pro798Leufs à 13 mutation caused the generation of premature termination of FV protein, subsequently, resulting in the formation of truncated protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be the reason for the decrease of FV:Ag in p.Asp2222Gly and p.Arg96His heterozygotes. The p.Pro798Leufs à 13 was first identified by Deng et al 5 , which suggested that it was a disease-causing mutation and might give rise to damage to the function and structure of the FV protein. According to our protein structure model, the p.Pro798Leufs à 13 mutation caused the generation of premature termination of FV protein, subsequently, resulting in the formation of truncated protein.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, 5 the calibrated automated thrombin (CAT) generation assay was used to examine thrombin generation. Following the protocol of the Thrombinoscope BV company (Rijswijk, the Netherlands), we measured the lag time, peak height, time to peak (ttPeak), and endogenous thrombin potential (ETP) to evaluate the procoagulant activity of FV on a Fluoroskan Ascent FL reading meter (Thermo Electron and Fisher Scientific Company, Waltham, Massachusetts, United States).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation